New Tale of Zatoichi Based on a Short Story by Kan Shimozawa - Tanaka, Tokuzô; Makiura, Chishi; Katsu, Shintaro; Tsubouchi, Mikiko; Kawazu, Seizaburô (Zatoichi: The Blind Swordsman Collection, 2019)
Zatoichi is back - and in color! Hoping to leave violence behind, the blind masseur wanders to a village, where he meets an old friend fallen on hard times. With a corrupt clan leader squeezing citizens dry and the brother of a past nemesis out for payback, Zatoichi finds that he cannot abandon his true calling. [www.criterion.com]